Sustaining cultural tourism through higher female participation in Nigeria: The role of corporate social responsibility in oil host communities - Joseph I. Uduji; Elda N. Okolo-Obasi; Simplice Asongu (African Governance and Development Institute (AGDI), 2019)
This paper adds to the gender discourse in sustainable African tourism development from the corporate social responsibility (CSR) perspective. Specifically, we examine the impact of CSR on the development of rural women in cultural tourism. A total of 600 rural women were sampled across the Niger Delta. Results from the use of a logit model indicate a significant relationship between CSR and cultural tourism development in oil host communities in Nigeria. This implies that CSR of a multinational oil company (MOC) is a critical factor for sustaining cultural tourism. The findings suggest increased female participation in General Memorandum of Understanding (GMoU) interventions of MOC and the need to pay close attention to which extent the participation of rural women in the GMoU projects may be limited by cultural and traditional obstacles.
Keywords: 330; Gender inequality; sustainable cultural tourism; corporate social responsibility; multinational oil companies; logit model; Nigeria